2009
DOI: 10.1002/pbc.22069
|View full text |Cite
|
Sign up to set email alerts
|

Health care utilization and expenditures for privately and publicly insured children with sickle cell disease in the United States

Abstract: Children with SCD enrolled in Medicaid had lower expenditures than privately insured children, despite higher utilization of medical care, which indicates lower average reimbursements. Research is needed to assess the quality of care delivered to Medicaid-enrolled children with SCD and its relation to health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 19 publications
5
63
1
Order By: Relevance
“…Although studies have shown that inpatient hospital, outpatient hospital, or emergency department visits did not differ significantly between a national sample of privately insured and Medicaidenrolled adults after controlling for health status and other factors [22], higher rates of health services utilization have been reported for Medicaid-enrolled children with SCD compared their privately insured counterparts [23]. We were also unable to identify the states from which the Medicaid sample was drawn and, therefore, could not assess the effects of regional variations in the management and treatment of SCD or pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have shown that inpatient hospital, outpatient hospital, or emergency department visits did not differ significantly between a national sample of privately insured and Medicaidenrolled adults after controlling for health status and other factors [22], higher rates of health services utilization have been reported for Medicaid-enrolled children with SCD compared their privately insured counterparts [23]. We were also unable to identify the states from which the Medicaid sample was drawn and, therefore, could not assess the effects of regional variations in the management and treatment of SCD or pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty to eighty percent of pediatric SCD patients are publically insured; and, dependent upon the state in which they live, there is a high potential that they will age out of Medicaid at age 18. Thus, many patients are left with no health insurance or they remain publically insured at the time of transition (Debaun & Telfair, 2012;Mvundura, Amendah, Kavanagh, Sprinz, & Grosse, 2009). Both scenarios are associated with poor health outcomes, including higher ED wait times, higher rehospitalization rates, higher numbers of acute care encounters and lower likelihood of getting an appointment with a specialty care provider (Agency for Healthcare Research and Quality, 2011;Bisgaier & Rhodes, 2011;Brousseau, Owens, et al, 2010).…”
Section: Factors Influencing Transitionmentioning
confidence: 99%
“…Another study showed that 18-30-year-olds had the highest average annual ED utilization rates compared to other age groups [15]. Furthermore, studies have demonstrated a higher average number of ED visits for uninsured patients with SCD compared to those who are privately insured [6,15]. However, there is limited information available about the influence of socioeconomic status on the use of health care services amongst patients with SCD.…”
Section: Journal Of Hematology and Thromboembolic Diseasesmentioning
confidence: 97%
“…patients with SCD [6,[14][15][16][17]. Based on the Thomas Jefferson University Hospital data, Epstein et al found that women had fewer hospitals ED visits but the difference between male and female officebased visits was not statistically significant [14].…”
Section: Journal Of Hematology and Thromboembolic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation